2013
DOI: 10.1089/end.2012.0535
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy Versus Ureteroscopic Lithotomy for Large (>15 mm) Impacted Upper Ureteral Stones in Different Locations: Is the Upper Border of the Fourth Lumbar Vertebra a Good Indication for Choice of Management Method?

Abstract: To determine whether treatment of patients with large (>15 mm) impacted upper ureteral stones depended on stone location, we prospectively evaluated the therapeutic outcomes, complications, safety, and effectiveness of percutaneous nephrolithotomy (PCNL) and ureteroscopic lithotomy (URSL) in patients with stones higher and lower than the upper border of the fourth lumbar vertebra. Of the 174 patients analyzed, 83 (47.7%) underwent PCNL and 91 (52.3%) underwent URSL; all patients were followed up 1 month later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
3
21
0
3
Order By: Relevance
“…These conclusions have been noted by previous researchers [7][8][9][10]. However, a number of authors believe that with large ureteral calculi the frequency of urethral injury and the percentage of ureteric stricture development in the antegrade approach are higher than in retrograde ureteroscopy [9,10]. To prevent these complications they recommend using a smaller caliber ureteroscope and avoiding the ureteral mucosal damage during lithotripsy, which is achieved using a flexible ureteroscope that usually has a smaller caliber than a rigid or semi-rigid ureteroscope, and using an ureteroscope with a casing can reduce friction between the mucosa ureter and ureteroscope.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These conclusions have been noted by previous researchers [7][8][9][10]. However, a number of authors believe that with large ureteral calculi the frequency of urethral injury and the percentage of ureteric stricture development in the antegrade approach are higher than in retrograde ureteroscopy [9,10]. To prevent these complications they recommend using a smaller caliber ureteroscope and avoiding the ureteral mucosal damage during lithotripsy, which is achieved using a flexible ureteroscope that usually has a smaller caliber than a rigid or semi-rigid ureteroscope, and using an ureteroscope with a casing can reduce friction between the mucosa ureter and ureteroscope.…”
Section: Resultssupporting
confidence: 88%
“…And the use of the nephroscope tube allows for large fragments of calculi evacuation that significantly reduces the time of operation. These conclusions have been noted by previous researchers [7][8][9][10]. However, a number of authors believe that with large ureteral calculi the frequency of urethral injury and the percentage of ureteric stricture development in the antegrade approach are higher than in retrograde ureteroscopy [9,10].…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Table 1 provides a description of the 14 studies. Of the 14 included studies, 7 compared URS with LU [1,9,12] , 4 compared URS with PCNL [10,13,18,19], and 3 compared URS with LU or PCNL [6,8,11] . Among these 7 studies that compared URS with LU, 3 studies used the retrograde intrarenal surgery (RIRS) technique in the URS group comparing with LU [2,12,20] .…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The mean size of stones ranged from 12 to 23 mm. Ten trials reported the presence of complications [2,7,[10][11][12][13][18][19][20][21] . The complication rate ranged from 4.1 to 33.8%.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%